GST AND THE INDIAN ECONOMY: OPPORTUNITIES, CHALLENGES, AND OUTCOMES - Mehta, CS Ekta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Goods and Services Tax (GST), implemented in India on 1st July 2017, is one of the most significant tax reforms in the nation’s economic history. Designed to replace a fragmented and complex indirect tax structure with a unified system, GST aims to simplify compliance, reduce the cascading effect of taxes, and create a seamless national market. This paper examines the concept, structure, and significance of GST, along with the opportunities, challenges, and outcomes associated with its implementation. The study highlights the reform’s role in fostering market integration, enhancing tax compliance through technology, and improving trade efficiency. It also addresses the hurdles encountered, such as technological glitches, rate complexity, and transitional issues for small businesses. While GST has already delivered notable benefits, including widening the tax base and strengthening fiscal transparency, its long-term success depends on continued policy refinement, rate rationalization, and stakeholder engagement. Overall, GST represents not merely a change in the taxation system, but a structural transformation with far-reaching implications for India’s economic growth and global competitiveness.